The Genome of a Mongolian Individual Reveals the Genetic Imprints of Mongolians on Modern Human Populations. (8th December 2014) - Bai, Haihua; Guo, Xiaosen; Zhang, Dong; Narisu, Narisu; Bu, Junjie; Jirimutu, Jirimutu; Liang, Fan; Zhao, Xiang; Xing, Yanping; Wang, Dingzhu; Li, Tongda; Zhang, Yanru; et al.
Abstract: Mongolians have played a significant role in modern human evolution, especially after the rise of Genghis Khan (1162[?]–1227). Although the social cultural impacts of Genghis Khan and the Mongolian population have been well documented, explorations of their genome structure and genetic imprints on other human populations have been lacking. We here present the genome of a Mongolian male individual. The genome was de novo assembled using a total of 130.8-fold genomic data produced from massively parallel whole-genome sequencing. We identified high-confidence variation sets, including 3.7 million single nucleotide polymorphisms (SNPs) and 756, 234 short insertions and deletions. Functional SNP analysis predicted that the individual has a pathogenic risk for carnitine deficiency. We located the patrilineal inheritance of the Mongolian genome to the lineage D3a through Y haplogroup analysis and inferred that the individual has a common patrilineal ancestor with Tibeto-Burman populations and is likely to be the progeny of the earliest settlers in East Asia. We finally investigated the genetic imprints of Mongolians on other human populations using different approaches. We found varying degrees of gene flows between Mongolians and populations living in Europe, South/Central Asia, and the Indian subcontinent. The analyses demonstrate that the genetic impacts of Mongolians likely resulted from the expansion of the Mongolian Empire in the 13th century. The genome will be of great help in further explorations of modern human evolution and genetic causes of diseases/traits specific to Mongolians.